Marca : evolução e proteção - um estudo comparativo entre as empresas Sadia e Perdigão - Menezes, Cláudia Cardinale Nunes (2014)
Over the years there have been major developments in corporate identity, which included the integration of the concept of the logo branding systems of both companies and products; extending thereby at the level of legal definitions or in the application forms, colors and uses of logos, as well as the design of the mark. Since then, the brand began to be considered one of the main intangible assets, providing the basis for a sustainable competitive advantage. Thus, the legal protection of this asset becomes indispensable. Considering the growth and importance of intangible assets |brand|, this study aimed to evaluate the profile of the trademark filing consolidated two Brazilian companies and national prominence in the food sector, including analysis of trademark protection since its evolution and extension the visual identity to the comparative study of management strategies relating to these distinctive signs. From data collected in the National Institute of Industrial Property for the years 2000 to 2013, exploratory-descriptive research was conducted, analyzing the evolution of marcarios records and protection of trademarks by the companies Sadia and Perdigao SA. According to the records, it was found that from the beginning to the present day, Perdigao brand and had a few minor alterations and identified records of change in mixed company brand in the years 1958, 1980 and 2005 On the other hand, for Sadia records modernization of its visual identification in the years 1960, 1993 and 2011, characterized by the association consumers make the brand together the stylized S and the image of the mascot were observed. The strategies of brands of both companies are extensions: line (creating different flavors and different features in various products); brand (using their names in different product categories, including meat products, pizza, snacks and pasta) and multi (insertion of brands introduced in the same product category market, such as margarines and Deline Qualy). Furthermore, firms make use of licensing strategies, for example: |Monica| (Sadia) and |The Smurfs| (Perdigao). As for the number of records was verified to occur in six different classes: 29, 30, 31, 32, 39, 43, however, with greater expressiveness in class 29, comprising 436 records of Sadia and Perdigao 162. However, 80% of the records of Sadia are active and 20% of applications filed, the total of 731 On the other hand, the 196 brands Perdigao 71% refers to the active. So mark protection is very important for both companies, evidenced by the high numbers of records over the years. Moreover, the construction of each brand was strategic element for both companies to consolidate the market, communicating its value proposition to consumers. It is noteworthy also that Sadia and Perdigao, during its existence, used strategies similar brands, however with regard to launching products, Sadia is still higher than Perdigao.